Candida associated infra-inguinal prosthetic vascular graft infection: A case report - Ahmet Deniz Kaya; Esma Nur Metin Kaya; Ihsan Alur (Turkish Journal of Vascular Surgery)
Prosthetic vascular grafts (PVG) are artificial vascular materials used for revascularization in the treatment of vascular diseases. Due to increase in life expectancy, the number of individuals requiring PVGs is increasing and encountering the PVGI is also more frequent. We presented an interesting case operated because of infected graft in which Candida albicans grew. The patient had been operated twice for peripheral artery disease in another hospital before. We performed femoro-popliteal bypass by using great saphenous vein after removal of infected graft. In peripheric bypass surgery performed with PTFE (polytetrafluoroethylene) graft, growth of Candida albicans in graft material is a rare condition and this situation has a high mortality rate. In the patients with comorbidities and who will undergo redo-surgery, excessive care should be given in terms of graft infections. [Turk J Vasc Surg 2024; 33(3.000): 186-8]